Electrochemically controlled switching of dyes for enhanced superresolution optical fluctuation imaging (EC-SOFI) - Ying Yang; Yuanqing Ma; Richard D. Tilley; J. Justin Gooding (Proceedings of the National Academy of Sciences, 2025)
In superresolution optical fluctuation imaging (SOFI), molecules spaced closer than the diffraction limit can be separated through spatial and temporal correlation analysis of the fluorescence intensity fluctuations. The resolution and speed of SOFI imaging greatly depend on the characteristics of these fluorescence fluctuations. Fluorophores with stochastic and rapid fluorescence fluctuations are favorable for improving SOFI imaging resolution and speed, especially in high-order cumulant analysis. Stochastic blinking of organic dyes in oxygen scavenging and thiol reducing buffers are well suited for SOFI due to their high brightness. However, the blinking rates can be too slow and nonuniform, which introduces nonlinearity in SOFI image. To address these challenges, we introduce electrochemically controlled dye switching for SOFI (EC-SOFI). By applying an oscillating electrochemical potential to a transparent electrode surface, we increase the overall dye switching rate and uniformity. Using Alexa 647 dye as an example, EC-SOFI reduces the average ON time by over threefold and switching variance by more than twofold compared to conventional photochemical switching, achieving ~60 nm spatial resolution in 6th order EC-SOFI image. We further demonstrate that EC-SOFI achieves ~130 nm and ~80 nm resolution with 100 and 300 frames, respectively, enabling fast, large-area tile-scan superresolution imaging. This advancement in EC-SOFI significantly enhances the practical potential of the SOFI technique.